Convex vNM-Stable Sets for linear production games - Joachim Rosenmüller; Benyamin Shitovitz (Bielefeld University, Institute of Mathematical Economics (IMW), 2008)
We characterize convex vNM-Stable Sets according to von Neumann and Morgenstern for orthogonal linear production games with a continuum of players. The results of Rosenmüller & Shitovitz [International journal of game theory 29 (2000), pp. 39-61] are thereby substantially improved. Simultaneously, this is a corrigendum concerning the proof of a lemma in our first paper.
urn:nbn:de:hbz:361-13712
Keywords: 330; Cooperative game theory; Coalitional function; vNM-stable set; Linear production games; Erwartungsnutzen; Spieltheorie; Rationales Verhalten; Entscheidungstheorie; Theorie